NONDESTRUCTIVE EVALUATION AND PREDICTION OF BENDING BEHAVIOR OF FIBER REINFORCED LAMINATED TIMBER - Vas, Zsigmond; Dénes, Levente (Innovation in Woodworking Industry and Engineering design, 2013)
This paper presents the results of a study conducted to investigate the bending properties of glue laminated timber reinforced with three different materials, jute fiber, glass fiber and carbon fiber respectively. To determine the modulus of elasticity and modulus of rupture both in flatwise and edgewise directions destructive and non-destructive testing methods were used. According to the results the strengthened beams show improved load-carrying capacity and energy absorption capacity by when compared to unstrengthened counterparts. It was further noted that the integrity of the bond depended not only on the adhesive used but also on the FRP type. The predicted MOE values had a good agreement with the static MOE values but the agreement varies in function of FRP type.